Still ‘Regime Competition’? Trade Unions and Multinational Restructuring in Europe - Pulignano, Valeria (Relations industrielles / Industrial Relations, 2006)
This article studies trade unions’ response to transnational change in a large multinational corporation within the motor industry in Europe. We show how the use of the European Works Councils (EWCs) as a forum for European negotiation did not counter the management’s effort to whipsaw trade unions, such as to play off workers against each other in local negotiations. This seems to suggest that the effort to network and coordinate between employee representatives, and to negotiate with management through ‘active’ EWCs is ineffective at controlling inter-union competition in cases of transnational restructuring. Hence, research outcomes illustrate that an analysis of the impact of European-level agreements on plant level is requested in order to assess the effectiveness of ‘active’ EWCs in forging cross-national links.